Injuries in elite level male beach soccer players: a prospective three year study - Lima, Y.; Bayraktar, B. (The Physician and Sportsmedicine, 2021)
Objectives The aim of this study was to investigate the incidence and characteristics of match and training injuries in elite-level national male beach soccer players.